2012
DOI: 10.1039/c2cy00422d
|View full text |Cite
|
Sign up to set email alerts
|

The average Pd oxidation state in Pd/SiO2 quantified by L3-edge XANES analysis and its effects on catalytic activity for CO oxidation

Abstract: The palladium oxidation state of an SiO 2 -supported palladium catalyst was quantitatively determined by Pd L 3 -edge XANES (X-ray absorption near-edge structure) analysis. By changing the time of CO-reduction pre-treatment at 673 K, a series of 5 wt% Pd-loaded SiO 2 catalysts (PdO x/2 /SiO 2 ) containing different amounts of the Pd metal and PdO phases were prepared, and the average oxidation number (x) was estimated from the number of CO 2 molecules formed during the CO-reduction treatment. L 3 -edge XANES s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…The spectral quality is clearly su cient for proper XANES analysis of both the Pd and Ag based samples. The spectral features of the L III edges are in line with previously reported data for both Pd catalysts [27] and Ag oxides [28]. Although these measurements were car- ried out under stationary air conditions at room temperature feeding of a reaction mixture through the reaction cell is not expected to significantly influence the quality of the spectra and thus these results demonstrate that relevant in situ experiments are possible also in fluorescence mode.…”
Section: B In Situ Transmission Xas Measurements Of the Pt LIII Edgesupporting
confidence: 89%
“…The spectral quality is clearly su cient for proper XANES analysis of both the Pd and Ag based samples. The spectral features of the L III edges are in line with previously reported data for both Pd catalysts [27] and Ag oxides [28]. Although these measurements were car- ried out under stationary air conditions at room temperature feeding of a reaction mixture through the reaction cell is not expected to significantly influence the quality of the spectra and thus these results demonstrate that relevant in situ experiments are possible also in fluorescence mode.…”
Section: B In Situ Transmission Xas Measurements Of the Pt LIII Edgesupporting
confidence: 89%
“…Metallic Pd 0 sites has been reported to act as catalytically active site for CO oxidation [10][11][12][13][14][15]. On the other hand, as mentioned above, metallic Pd 0 sites, which was formed by H 2 reduction as a pretreatment, supported on Al 2 O 3 is partly oxidized to PdO x during the oxidation reaction, leading to the different Pd 0 /PdO x ratio depending on the Pd dispersion.…”
Section: Co Oxidation Reactionmentioning
confidence: 94%
“…For example, Satsuma et al [10,11] evaluated the reaction rate for CO oxidation over Pd/SiO 2 having various average oxidation number of PdO x , and observed that the CO oxidation activity of PdO x /SiO 2 was steeply decreased with the increase in the x value in PdO x . They concluded that the metallic Pd 0 is the active species for CO oxidation over Pd/SiO 2 .…”
Section: Introductionmentioning
confidence: 98%
“…S11†). 43 Based on comparison of the edge energy for Pd 3 (OAc) 6 , Pd 3 btei, PdZn(OAc) 4 , and Pd metal, the edge energy is inconsistent with the presence of Pd(0) in the exchanged samples.…”
Section: Resultsmentioning
confidence: 99%